Relevant business statistics : using Excel - Gerbing, David W. (Cincinnati, OH : South-Western College, 1999)
This book presents: Variables and Data; Portraying the Values of a Distribution; Numerical Summaries of a Distribution; Confidence Interval around a Mean...
Keywords: Methodology; Commercial statistics; Computer programs; Microsoft Excel for Windows; Commercial statistics -- Methodology -- Computer programs; Microsoft Excel for Windows